Factors participating in the development and mortality of variceal bleeding in portal hypertension - possible effects of the kidney damage and malnutrition - Lata, Jan; Husová, Libuše; Juránková, Jana; Šenkyřík, Michal; Dítě, Petr; Dastych, Milan; Dastych, Milan; Kroupa, Radek (Hepato-gastroenterology, 2006)
BACKGROUND/AIMS: Acute bleeding from esophageal varices due to portal hypertension is a frequent and severe complication of liver cirrhosis. The development of esophageal varices as well as their rupture depends on the level of portal pressure; however, a number of other factors may play a negative role in the rise of bleeding and its prognosis. METHODOLOGY: The report presented has compared a set of 46 patients admitted to hospital for acute bleeding with 48 cirrhotics hospitalized for other reasons. RESULTS: Bleeding patients had significantly higher level of nitrogenous substances (urea 14.1 mmol/L vs. 7.78 mmol/L, p < 0.01, creatinine 129.8 micromol/L vs. 106.04 micromol/L; p = 0.09). The disturbed renal function in itself probably does not increase the risk of bleeding, it may be rather considered a certain prognostic index of the portal hypertension degree. Bleeding patients had a lower level of total protein (60.7 g/L vs. 69.9 g/L; p < 0.01) with only slight insignificant decrease of albumin (26.64 g/L vs. 28.51 g/L). Cirrhotic patients are known to suffer from malnutrition and it is possible that malnutrition shares negatively and directly in the rise of bleeding. CONCLUSIONS: A prognostic index of mortality was a more conspicuous disorder of hepatic function (bilirubin 97.4 micromol/L vs. 57.4 micromol/L; p = 0.1; prolonged prothrombin time 1.99 INR vs. 1.56 INR; p = 0.01) and again the disorder of renal function (creatinine 166.7 micromol/L vs. 114.9 micromol/L; p = 0.09). Therefore, the maintenance of good renal function must be a component of complex therapy given to bleeding patients.
Keywords: nemoci ledvin; financování organizované; dospělí; Bilirubin; Hypertension, Portal; portální hypertenze; Female; Esophageal and Gastric Varices; močovina; ezofageální a žaludeční varixy; Liver Cirrhosis; Adult; ženské pohlaví; Malnutrition; Urea; jaterní cirhóza; lidé; Survival Analysis; gastrointestinální krvácení; Gastrointestinal Hemorrhage; podvýživa; Aged, 80 and over; Kidney Diseases; Financing, Organized; Risk Factors; Hematocrit; Male; Prothrombin Time; Aged; protrombinový čas; rizikové faktory; bilirubin; analýza přežití; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; hematokrit; Middle Aged; Humans